Apples and oranges: explorations in, on, and with comparison - Lincoln, Bruce (The University of Chicago Press, 2018)
Intro -- Contents -- List of Figures and Tables -- Acknowledgments -- I. General Observations -- 1. Introduction -- 2. The Future of History of Religions -- 3. Theses on Comparison -- II. Recent Attempts at Grand Comparison -- 4. The Werewolf, the Shaman, and the Historian -- 5. The Lingering Prehistory of Laurasia and Gondwana -- III. A Comparatist's Laboratory: The Ancient Scythians -- 6. Reflections on the Herodotean Mirror: Scythians, Greeks, Oaths, and Fire -- 7. Greeks and Scythians in Conversation -- 8. Scythian Priests and Siberian Shamans -- IV. Weak Comparisons -- 9. Further on Envy and Greed -- 10. King Aun and the Witches -- 11. Contrasting Styles of Apocalyptic Time -- 12. Sly Grooms, Shady Magpies, and the Mythic Foundations of Hierarchy -- 13. In Hierarchy's Wake -- Notes -- Bibliography -- Index